Practical Implementation of Light Ion Beam Treatments. Issue 1 (26th December 2013) - Cheng, Chee‐Wai
Abstract : Practical Implementation of Light Ion Beam Treatments. Moyers Michael F., Vatnitsky Stanislav M., Medical Physics Publishing, Madison, WI, 2012. 580 pp. Price: 175.00. ISBN 978‐1‐930524‐55‐2 (hardcover)/978‐1‐930524‐59‐0 (CD).